Implementasi Middleware Laravel untuk Akses Multi-User : Studi Kasus Sistem Berita Acara Perkuliahan - Tan, Robby (Jurnal Teknik Informatika dan Sistem Informasi, 2025)
One of the lecturers’ roles in Tridharma is teaching. There is a shift in the role of lecturers where lecturers are not only compiling and delivering materials but also guiding students in class so that they can think actively and independently. Universities must record teaching activities carried out by lecturers. Documentation of teaching activities is carried out using lecture minutes in either hardcopy or online form. There are problems faced in the digital recording process, namely data duplication due to the absence of data history, long data entry, and the difficulty of recapitulating required data. To solve the problem, a system is needed that can handle the data input process and share access so lecturers, vice deans, or faculty administrators can monitor the activities carried out. The system is built using the Laravel framework, which utilizes object-relational mapping (ORM) and middleware. ORM is used to simplify class attributes and relations between classes. The contents of classes designed with ORM are simpler than classes created conventionally. Middleware is a class that functions to process HTTP Requests. HTTP Requests can be validated for authentication processes and web access settings. The implementation has divided the user roles, namely lecturers, faculty vice deans, faculty/department level administrators, and administrators. Each role has its specific functions. Lecturers can only enter lecture minutes (BAP) for assigned courses and can monitor the data. The BAP input process also cannot be delegated to other parties. Faculty/department administrators and vice deans can monitor the BAP input process and confirm data according to the level given. Confirmed data can be exported in another form to facilitate the subsequent reporting process.